Strategic infarct location for post-stroke cognitive impairment: A multivariate lesion-symptom mapping study. Issue 8 (August 2018) - Zhao, Lei; Biesbroek, J Matthijs; Shi, Lin; Liu, Wenyan; Kuijf, Hugo J; Chu, Winnie WC; Abrigo, Jill M; Lee, Ryan KL; Leung, Thomas WH; Lau, Alexander YL; Biessels, Geert J; Mok, Vincent; et al.
Lesion location is an important determinant for post-stroke cognitive impairment. Although several 'strategic' brain regions have previously been identified, a comprehensive map of strategic brain regions for post-stroke cognitive impairment is lacking due to limitations in sample size and methodology. We aimed to determine strategic brain regions for post-stroke cognitive impairment by applying multivariate lesion-symptom mapping in a large cohort of 410 acute ischemic stroke patients. Montreal Cognitive Assessment at three to six months after stroke was used to assess global cognitive functioning and cognitive domains (memory, language, attention, executive and visuospatial function). The relation between infarct location and cognition was assessed in multivariate analyses at the voxel-level and the level of regions of interest using support vector regression. These two assumption-free analyses consistently identified the left angular gyrus, left basal ganglia structures and the white matter around the left basal ganglia as strategic structures for global cognitive impairment after stroke. A strategic network involving several overlapping and domain-specific cortical and subcortical structures was identified for each of the cognitive domains. Future studies should aim to develop even more comprehensive infarct location-based models for post-stroke cognitive impairment through multicenter studies including thousands of patients.